2016
DOI: 10.1371/journal.pntd.0004591
|View full text |Cite
|
Sign up to set email alerts
|

GPS Tracking of Free-Ranging Pigs to Evaluate Ring Strategies for the Control of Cysticercosis/Taeniasis in Peru

Abstract: BackgroundTaenia solium, a parasitic cestode that affects humans and pigs, is the leading cause of preventable epilepsy in the developing world. T. solium eggs are released into the environment through the stool of humans infected with an adult intestinal tapeworm (a condition called taeniasis), and cause cysticercosis when ingested by pigs or other humans. A control strategy to intervene within high-risk foci in endemic communities has been proposed as an alternative to mass antihelminthic treatment. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…This mechanism of within-household transmission of T. solium from human carriers to their pig herd is consistent with a GPS tracking study previously conducted by our group in this region. 23 In that study, we found that both pig roaming patterns and reported human defecation locations were concentrated in the immediate vicinity of households, highlighting the potential for focal transmission through exposure to T. solium eggs in cases where the pig owner has taeniasis.…”
Section: Discussionmentioning
confidence: 73%
“…This mechanism of within-household transmission of T. solium from human carriers to their pig herd is consistent with a GPS tracking study previously conducted by our group in this region. 23 In that study, we found that both pig roaming patterns and reported human defecation locations were concentrated in the immediate vicinity of households, highlighting the potential for focal transmission through exposure to T. solium eggs in cases where the pig owner has taeniasis.…”
Section: Discussionmentioning
confidence: 73%
“…Despite this strength, CystiAgent only begins to account for the complex heterogeneities that likely occur in real-world systems. Age-related differences in pig roaming patterns [23], seasonal and climate-related variations in transmission [44], acquired immunity and resistance among pigs [45], vector-borne transmission of T. solium eggs to pigs [46,47], and black-market distribution of infected pork [48] are only a few of the many additional factors that may impact transmission patterns and are not explicitly defined in CystiAgent. Additional data from experimental or field studies and will be needed in order to incorporate these features into future versions of the model and evaluate their impact on transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Local variations in pig-raising practices, sanitation, diet, and migration all interact to create locally specific transmission patterns that differ from one endemic village to the next [20]. Even within villages, spatial heterogeneities caused by pig-roaming patterns and open defecation cause clustering that is important for a model to capture [21][22][23]. Importantly, incorporating underlying spatial and biological processes of T. solium transmission was highlighted in a recent report on the WHO 2030 goals [13], and there is evidence that models that fail to account for these heterogeneities are susceptible to overestimating the effect of control interventions [24] and yielding unrealistic predictions for achieving control and elimination targets [25].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this strength, CystiAgent only begins to account for the complex heterogeneities that likely occur in real-world systems. Age-related differences in pig roaming patterns [20], seasonal and climate-related variations in transmission [41], acquired immunity and resistance among pigs [42], vector-borne transmission of T. solium eggs to pigs [43,44], and black-market distribution of infected pork [45] are only a few of the many additional factors that may impact transmission patterns and are not explicitly de ned in CystiAgent. Additional data from experimental or eld studies and will be needed in order to incorporate these features into future versions of the model and evaluate their impact on transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Local variations in pig-raising practices, sanitation, diet, and migration all interact to create locally speci c transmission patterns that differ from one endemic village to the next [17]. Even within villages, spatial heterogeneities caused by pig-roaming patterns and open defecation cause clustering that is important for a model to capture [18][19][20]. Importantly, incorporating underlying spatial and biological processes of T. solium transmission was highlighted in a recent report on the WHO 2030 goals [11], and there is evidence that models that fail to account for these heterogeneities are susceptible to overestimating the effect of control interventions [21] and yielding unrealistic predictions for achieving control and elimination targets [22].…”
Section: Introductionmentioning
confidence: 99%